CLINICALLY INVISIBLE RETINAL HEMANGIOBLASTOMAS DETECTED BY SPECTRAL DOMAIN OPTICAL COHERENCE TOMOGRAPHY AND FLUORESCEIN ANGIOGRAPHY IN TWINS. Issue Volume 12:Issues 1(2018) (2018) - Schoen, Marisa A.; Shields, Carol L.; Say, Emil Anthony T.; Douglass, Alexzandra M.; Shields, Jerry A.; Jampol, Lee M.
Abstract : Purpose: To report subclinical retinal hemangioblastoma detected by enhanced depth imaging optical coherence tomography and fluorescein angiography in at-risk twins. Methods: Case report. Results: A set of twins, age 7 years, (Twin A and Twin B) with known family history of von Hippel–Lindau disease (gene test positive) and no systemic manifestations were evaluated. Visual acuity was 20/20 in both eyes of both twins. Anterior segment examination and intraocular pressures were unremarkable in both eyes. Twin A showed no clinically visible tumor in the right eye, and a clinically evident 4-mm hemangioblastoma in the superior retina of the left eye. The enhanced depth imaging optical coherence tomography demonstrated normal fovea in both eyes. However, imaging at the inferonasal juxtapapillary region in the right eye documented an intraretinal mass from nerve fiber layer to outer plexiform layer on enhanced depth imaging optical coherence tomography and with hyperfluorescence on fluorescein angiography, consistent with retinal hemangioblastoma. Twin B demonstrated no clinically visible tumors in both eyes, but the left eye showed a small hyperreflective lesion in the parafoveal region on spectral domain optical coherence tomography from inner to outer nuclear layers, with no cystoid changes or subretinal fluid. The lesion was slightly hyperfluorescent on fluorescein angiography, consistent with hemangioblastoma. The optical coherence tomography angiography showed no vascularity within the lesion. Twin A was treated with laser photocoagulation to the larger hemangioblastoma in the left eye, and the asymptomatic juxtapapillary tumor was observed. Twin B was managed with cautious observation as treatment to the left eye could lead to vision loss. Conclusion: Patients at risk for retinal hemangioblastoma should have routine imaging with fundus photography, fluorescein angiography, and enhanced depth imaging optical coherence tomography for subclinical detection of asymptomatic tumors. Abstract : Patients at risk for retinal hemangioblastoma should have routine imaging with fundus photography, fl uorescein angiography, and enhanced depth imaging optical coherence tomography for subclinical detection of asymptomatic tumors.